Galactosidase Alpha p.A143T Variant Fabry Disease May Result in a Phenotype With Multifocal Microvascular Cerebral Involvement at a Young Age - Hauth, Lothar; Kerstens, Jeroen; Yperzeele, Laetitia; Eyskens, François; Parizel, Paul M.; Willekens, Barbara (Frontiers in Neurology, 2018)
Introduction A 16-year-old male presented with episodic headaches and a brain magnetic resonance imaging (MRI) that showed multifocal punctate to patchy white matter lesions. The diagnosis of Fabry disease (FD) was suggested upon the finding of significantly reduced plasma alpha-galactosidase A activity (0.62 µmol/L or 13% of normal; normal range ≥ 1.65 μmol/L) and genetic investigation confirmed the presence of a hemizygous missense variant in the galactosidase alpha (GLA) gene (p.A143T). Baseline assessment of other systemic involvement showed only a discrete proteinuria. Background FD is a rare lysosomal storage disorder. Genetic screening studies have revealed over 600 variants in the GLA gene. The p.A143T variant is a genetic variant of unknown significance, with its associated phenotype ranging from classical FD to healthy unaffected patients. Some authors, however, deem this variant non-pathogenic. We describe the case of a 16-year-old male with multifocal white matter lesions on brain MRI, who was diagnosed with FD and carried this genetic variant. Discussion The causative p.A143T mutation can be associated with a more severe subclinical phenotype than has been reported to date. Furthermore, a diagnosis of FD should be considered when finding asymptomatic cerebral white matter lesions in a young patient.